Pengaruh Leverage Dan Profitabilitas Terhadap Agresivitas Pajak Pada Bank Umum Konvensional Di Bursa Efek Indonesia - Selina Putri Pamungkas; Indria Widyastuti (Jurnal Intelek Insan Cendikia, 2024)
There is a negative and significant influence between the Debt to Equity Ratio (DER) leverage variable on the Effective Tax Rate (ETR) variable in conventional banks listed on the Indonesian Stock Exchange (BEI) for the 2020-2022 period. There is no and insignificant influence on Profitability Return on Assets (ROA) on Tax Aggressiveness Effective Tax Rate (ETR) in conventional banks listed on the Indonesian Stock Exchange (BEI) for the 2020-2022 period. There is a positive and significant influence between Debt to Equity Rati (DER) leverage and Return On Asset (ROA) profitability on Tax Aggressiveness Effective Tax Rate (ETR) in conventional banks listed on the Indonesian Stock Exchange (BEI) for the 2020-2022 period.